Academic Senate Minutes 2001-12-13 - Academic Senate:::::::::
Agenda and Minutes approved. Consent items of Computer Science Curriculum revision and Global Studies Concentration in Asian Studies approved. Diversity Vision statement approved. Three resolutions from the Senate Budget Committee presented. Resolution regarding Development Office divided. First resolved tabled. Second resolved failed. Presentation on the Green Music Center from Bernie Goldstein, Jeff Langley and Floyd Ross. No reports.